SELECTED BASIC MATHEMATICAL AND STATISTICAL CONCEPTS IN THE ANALYSIS OF CAPITAL INVESTMENT - Igor Sehanovic (Journal of Business Paradigms, 2016)
In this paper, we are mainly dealing with the illustration of how business math can be used in practice in analyses that are an integral part of the preparation of investment projects (most often in fixed tangible assets, plant, equipment, etc.). Preparation of investment projects is always based on certain assumptions (description, table of contents, location of delivery/consumption, shape, design, quality… products/services) for which it is necessary to create a material component (land, buildings, machinery…) and a human component (workers, bosses, managers…) to manufacture (yes, and services are produced) and sell the same. Production and sales result in costs (expenditures) and income. Other than the aforementioned, planning takes place on a daily basis for all variables, and these plans are categorized into the annual and the multi-annual (because investment produces multi-annual business/investment results, and these results should be planned and analyzed in order to determine the efficiency of investments and their justification/acceptability for the investors/company). We can also prepare financial investments and analyze them as an investment in fixed tangible assets. Depending on the activity, preference for risk/refund, state of the market – enterprises, banks, investment funds, insurance companies… investments are structured into fixed material assets, i.e., long-term financial investments